Review of PRGF-HIPC Financing, the Adequacy of the Reserve Account of the PRGF Trust, and Subsidization of Emergency Assistance. (Policy Papers; Policy Paper, 2005)
Provides the basis for the semi-annual decision on the adequacy of the Reserve Account of the PRGF Trust. It also updates the status of resources for financing PRGF operations and the HIPC Initiative and bilateral contributions to the subsidization of emergency assistance.